Acute injuries and chronic disorders in competitive surfing. From the survey of professional surfers in Japan - Inada, K.; Matsumoto, Y.; Kihara, T.; Tsuji, T.; Netsu, M.; Kanari, S.; Yakame, K.; Arima, S. (Sport-Orthopädie - Sport-Traumatologie, 2018)
Background: There have been very few published reports which concerns sports-related acute injuries and chronic disorders sustained during surfing. Therefore, we have been making survey of professional surfers certified by Japan Pro Surfing Association (JPSA) since 2009. Materials and methods: Data were collected through the survey of professional surfers certified by JPSA at the competitions and our outpatient clinic. Results: Acute injuries during surfing competitions were rare, and commonly happened at lower extremities. Knee MCL injuries, foot and ankle ligamentous injuries were remarkable for lower extremity. Especially, midfoot injuries would be characteristic of competitive surfing, because those injuries happen in aerial manoeuvres which is too difficult to perform for recreational surfers. Chronic disorders of competitive surfers were seen in lower back, shoulder joint, and neck areas. Most of the disorders were diagnosed as myofascitis caused by overuse of muscles during long-time paddling. Conclusions: Our results are substantially different from the results of a survey of recreational surfers, and appear to be reflective of the competitive characteristics of surfing.